Upper Six Students' Perceptual Language Learning Styles Preferences and Language Learning Strategies in Their Preparation for Malaysian University English Test (MUET). - Daniel, Francis Xavier Klumai (Universiti Malaysia Sarawak (UNIMAS), 2008)
This study aimed to investigate the perceptual learning style preferences and language learning strategies of Upper Six students in urban and rural schools as they prepared for Malaysian English Test (MUET). The objectives of the study are to investigate the learning styles and learning strategies base on school location, gender and races of the students from urban and rural eight selected schools. Six types of learning styles and six types of learning strategies were being investigated in this study. Learning styles involved were known as visual, tactile, auditory, kinesthetic, group and individual styles while the other six learning strategies were memory, cognitive, compensation, metacognitive, affective and social. Data were collected through questionnaires and distributed to 200 students. The findings showed that all of the learning styles were major learning styles used by the Upper Six students and group learning style was the most preferred. As for learning strategies, all of them were high used by the students. However, metacognitive appeared to be the highest used learning strategies as they prepared for MUET. The statistical tests indicated that the Upper Six preference learning styles and learning strategies were not influenced by their school location, gender and races. The survey results also showed that individual learning style and affective learning strategies were less preferred by them. Though, there was a difference of mean in their learning styles and learning strategies involved but all of them were their major learning styles and highly used learning strategies by the Upper Six students. As a result, it suggested that there was no clear relationship between the learning styles and learning strategies but the students themselves to be more aware of the differences in learning so as to attain meaningful learning.